A Profile of Living Standards in Turkmenistan - World Bank (Washington, DC, 2013)
The study reviews the living standards in Turkmenistan, shaped by the Soviet legacy - whose income levels in 1989 were below the socially acceptable minimum -; by the economic decline throughout the 1990s, until recent economic resumption; and, by current approaches, and government policies. In an attempt to ensure good living standards, the country maintained one of the highest levels of subsidization of basic goods: water, gas, fuel, and social services, are mostly free. To some extent, the poor do benefit from these subsidies, but troubling issues reveal that: the costs of these non-targeted subsidies are not transparent, because they are paid by the providing agency, which in turn receives subsidized inputs. Nonetheless, real costs make it impossible to operate on a commercial basis, and, the non-payment system as it relates to maintenance and operation, has led to poor quality of services. But poverty alleviation implies much more than just subsidies, for measured in access to opportunity, it is seriously limited: few mechanisms exist for enabling the poor to benefit from most of the country's energy export earnings. Based on evidence that funding for social services represent transparent expenditures, and that subsidized commodities are disproportionately benefiting the wealthy, the potential for commercialization is undermined, unless services move to market pricing standards.